Freshwater ecosystems - Gagne, Tammy (Earth's ecosystems., 2018)
Explores the unique features of a freshwater ecosystem, offering information on where in the world these can be found and what kinds of animals and plants live there. Also discusses ways to conserve freshwater ecosystems. Includes color photographs, critical thinking questions, statistics, a color diagram, a glossary, and further resources.